2016
DOI: 10.1159/000444075
|View full text |Cite
|
Sign up to set email alerts
|

Meconium Evacuation for Facilitating Feed Tolerance in Preterm Neonates: A Systematic Review and Meta-Analysis

Abstract: Background: A delayed passage of meconium is considered as a risk factor for feed intolerance in preterm neonates. Objectives: The aim of this study was to review the effects of different therapeutic agents for meconium evacuation on feed tolerance in preterm neonates. Methods: A systematic review of randomised controlled trials (RCTs) of different therapeutic agents for meconium evacuation in preterm neonates (gestation <32 weeks and/or birth weight <1,500 g) using the Cochrane systematic review methodology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In a meta-analysis of 6 studies using different forms of meconium evacuation strategies, there was no effect on NEC (RR 1.71, 95% CI 0.63–4.65, 6 studies, 442 infants) but there was a trend towards increasing risk with oral gastrographin administration (RR 2.61, 95% CI 0.88–7.74, 1 study, 96 infants). 62 A review of only glycerin laxative enemas or suppositories showed no effect on NEC (RR 2.75, 95% CI 0.58–13.1, 2 studies 96 infants), although the point estimate suggested a greater probability of harm than benefit in the risk of NEC with use of glycerin. 63…”
Section: F Postnatal Factorsmentioning
confidence: 99%
“…In a meta-analysis of 6 studies using different forms of meconium evacuation strategies, there was no effect on NEC (RR 1.71, 95% CI 0.63–4.65, 6 studies, 442 infants) but there was a trend towards increasing risk with oral gastrographin administration (RR 2.61, 95% CI 0.88–7.74, 1 study, 96 infants). 62 A review of only glycerin laxative enemas or suppositories showed no effect on NEC (RR 2.75, 95% CI 0.58–13.1, 2 studies 96 infants), although the point estimate suggested a greater probability of harm than benefit in the risk of NEC with use of glycerin. 63…”
Section: F Postnatal Factorsmentioning
confidence: 99%
“…As a result of definition problems and lack of standard approaches to MIPI, there are not enough clinical trails addresses to reach early full enteral feedings in very low-birth weight infants with MIPI (17). There are only six trials in a recent metaanalysis and all have the small sample size and some of them heterogenic (17).…”
Section: Discussionmentioning
confidence: 99%
“…As a result of definition problems and lack of standard approaches to MIPI, there are not enough clinical trails addresses to reach early full enteral feedings in very low-birth weight infants with MIPI (17). There are only six trials in a recent metaanalysis and all have the small sample size and some of them heterogenic (17). As a result of these limitations this recent systematic review suggested that the use of a glycerine suppository, small-volume enema with glycerine or normal saline, or the administration of an oral osmotic agent, such as gastrografin, to evacuate the meconium did not reduce the time to reach full enteral feeds in very low birth weight neonates (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…His daily abdominal X-ray indicated significantly expanding intestinal gas, and we diagnosed him with meconium-related ileus. Intragastric administration of 3 mL/kg 5-fold-diluted amidotrizoic acid succeeded in triggering mass excretion of feces, as described in previous studies (31)(32)(33)(34)(35). Subsequently, abdominal distention improved, and enteral feeding was resumed.…”
Section: Case Descriptionmentioning
confidence: 69%